The Theoretical and Legal Foundations of Privacy in the Public Sphere - Simonović, Ivana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2026)
This paper examines the evolution of privacy from a classic right to be let alone to a dynamic, multidimensional civil subjective right. Analyzing privacy as an umbrella concept that safeguards personal integrity, autonomy, and dignity, the study categorizes its various manifestations through the intimate, private, and individual spheres. Special emphasis is placed on informational privacy and the four freedoms (bodily, mental, decisional, and informational), which serve as essential protections against the pervasive risks of information and communication technologies. The author argues that personal data protection functions as a technical˗legal concretization of privacy, transforming abstract values into practical mechanisms within the framework of the GDPR and national legislation. Furthermore, the paper addresses the civil law challenges of protecting personal attributes and privacy in public spaces, highlighting the multiplicative and permanent nature of digital violations.
Keywords: P﻿rivacy; informational autonomy; data protection; Civil Law; public sphere; legitimate expectation of privacy; intrusion